2017
DOI: 10.22159/ijap.2017v9i6.22556
|View full text |Cite
|
Sign up to set email alerts
|

Enzymosomes: A Rising Effectual Tool for Targeted Drug Delivery System

Abstract: The study aims to develop enzymosomes as an emerging novel drug delivery system for site-specific action. Enzymosomes utilises the specific nature of an enzyme, which is binding to a specific substrate at a controlled rate and catalysing product production step. An enzyme is encapsulated by coupling covalently to the surface of liposomes/lipid vesicles to form enzymosomes. Enzymes links through acylation, direct conjugation, physical adsorption, encapsulation methods to prepare enzymosomes with targeted action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…99 In Crohn's disease, there is an increase in mucus production thus paving way of attachment of nanoparticles to thick mucus layer more strongly and leads to detention of drug to diseased colitis tissue. 100 A supportive base for muco-adhesive nanodrug delivery system was suggested by Niebel et al who found that clodronate alone was ineffective in colitis therapy but proved efficient when it was combined with cationic nanoparticle polymethacrylate. 101 Colon drug targeting using liposomes The use of liposomes as carriers has improved drug delivery to colon.…”
Section: Nanodrug Delivery System Based On Sizementioning
confidence: 99%
“…99 In Crohn's disease, there is an increase in mucus production thus paving way of attachment of nanoparticles to thick mucus layer more strongly and leads to detention of drug to diseased colitis tissue. 100 A supportive base for muco-adhesive nanodrug delivery system was suggested by Niebel et al who found that clodronate alone was ineffective in colitis therapy but proved efficient when it was combined with cationic nanoparticle polymethacrylate. 101 Colon drug targeting using liposomes The use of liposomes as carriers has improved drug delivery to colon.…”
Section: Nanodrug Delivery System Based On Sizementioning
confidence: 99%